2019
DOI: 10.15611/aoe.2019.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Upper tail of the income distribution in tax records and survey data. Evidence from Poland

Abstract: Growing interest in the situation of the rich and in changes in the upper tail of the income distribution entails search for specialized sources of data. The majority of available data come from surveys, which are burdened with the problem of the reluctance of the rich to reveal their income and assets. This is the incentive to look for alternative data sources. One of such sources are tax records. Irrespective of their credibility (limited by tax avoidance and tax evasion), the crucial feature of data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In our accompanying work in progress (Bukowski et al, 2021 ) we show that the above methodology produced series on income inequality remarkably similar to those based on the registry database of the universe of individual-level tax returns for the period 2004–2017 (see also Kośny, 2019 for Lower Silesia).…”
Section: Methodsmentioning
confidence: 58%
“…In our accompanying work in progress (Bukowski et al, 2021 ) we show that the above methodology produced series on income inequality remarkably similar to those based on the registry database of the universe of individual-level tax returns for the period 2004–2017 (see also Kośny, 2019 for Lower Silesia).…”
Section: Methodsmentioning
confidence: 58%
“…More methodological details on Polish HBS may be found in Główny Urząd Statystyczny -Statistics Poland (2015). For a brief description of the tax data in Poland applicable to this study see Kośny (2019).…”
Section: The Data Issuesmentioning
confidence: 99%
“…For a comprehensive discussion of household survey measurement errors see Moore et al (2000) and Kasprzyk (2005), while nonresponse issues are discussed in Lepkowski (2005). A discussion of the Polish household survey data quality may be found in Kośny (2019). Generally, two approaches to handling the data errors in research on inequality and poverty may be observed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…8 We use the modified OECD equivalence scale. 9 Kośny (2019) provides top income shares estimated from individual tax returns for Lower Silesian Voivodeship in Poland. 10 Information from individual tax returns from Poland is not at present available to researchers.…”
Section: Polish Household Budget Survey (Phbs) Datamentioning
confidence: 99%